The Impact of Foreign Direct Investment (FDI) on Economic Growth and Development in Nigeria: Prospects, Challenges, and Policy Implications - KALU, Benjamin Okezie; IJIOMAH, Amarachukwu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Foreign direct investment (FDI) has long been viewed as a vital component of economic growth in developing countries, particularly in Nigeria, Africa's largest economy. This paper explores the complex relationship between FDI and Nigeria's economic development, highlighting both the potential benefits and challenges. FDI contributes capital, technology transfer, and expertise, which can diversify the economy and create employment. However, it also poses risks such as capital flight, environmental degradation, and cultural homogenization. Using empirical studies and case analyses, the paper examines the determinants of FDI inflows and outflows, the role of institutional and legal frameworks, and the impact of foreign capital on Nigeria’s economic trajectory. Additionally, the research outlines the critical challenges, including corruption, infrastructure deficits, and regulatory hurdles, while offering insights into policy strategies aimed at optimizing FDI for sustainable growth.